Frequency of Common Bile Duct Injury in Open Cholecystectomy versus Laparoscopic Cholecystectomy - Pirah; Sarika; Ahmed, Anila; Mariam; Fatima, Anum; Kamran, Muhammad; Sami, Muskan (Indus Journal of Bioscience Research, 2025)
Background: Laparoscopic cholecystectomy has replaced open cholecystectomy as the standard treatment for cholelithiasis. However, it is associated with a higher incidence of common bile duct (CBD) injury. (LC) has become the preferred treatment for cholelithiasis; however, it carries a higher risk of common bile duct (CBD) injury compared to open cholecystectomy. It is a largely replaced open cholecystectomy (OC) but is associated with higher rates of common bile duct (CBD) injury. This study compares the frequency of CBD injury between the two techniques. To compare the frequency of CBD injury in open cholecystectomy versus laparoscopic cholecystectomy. Methodology: A randomized controlled trial was conducted at the Department of Surgery, People Medical College Hospital Nawabshah, from July 1 to December 31, 2020. A total of 320 patients aged 20–50 years with cholelithiasis were randomly divided into two groups: 160 underwent open cholecystectomy and 160 laparoscopic cholecystectomy CBD injuries were diagnosed clinically (jaundice) and confirmed via MRCP. Frequency of CBD injury was observed and analyzed statistically using SPSS 22.0, with significance at p ≤ 0.05. Results: Out of 320 patients (160 in each group) Mean age was 33.5±8.7 years; 54.7% were female, CBD injury was observed in 3.8% of patients in the open cholecystectomy group compared 9.4% of the laparoscopic group. The difference was statistically significant (p = 0.042). Indicating a significantly higher rate in laparoscopic procedures and those with diabetes had higher injury rates in the LC group. Conclusion: Laparoscopic cholecystectomy is associated with a higher frequency of CBD injury compared to open cholecystectomy. Enhanced surgical training and safety protocols are essential.